Predictions of TeV emission for a set of hard BL Lac objects. Issue 4 (12th October 2021) - Paiano, Simona; Treves, Aldo; Franceschini, Alberto; Falomo, Renato
ABSTRACT: We focus our analysis on 55 BL Lac objects with a hard Fermi gamma-ray spectrum, and for which a redshift or a lower limit to it has been determined by a previous study of ours. We extrapolate the spectral fits given by the 4FGL catalogue to the VHE band (>0.1 TeV), which can be explored by imaging atmospheric Cherenkov telescopes. Furthermore, we take into account the absorption due to the extragalactic background light, strongly depending on the redshift. Finally, we compare our results with publicly available sensitivity curves for a selection of imaging atmospheric Cherenkov telescope arrays currently operating or under construction. From our extrapolations and simulations we find a large number of promising candidates for observation with the forthcoming Cherenkov Telescope Array observatory.